Земства України на тлі суспільно-політичних процесів доби Центральної Ради (березень 1917 р. – квітень 1918 р.) - Матвієнко, Т.О.; Матвиенко, Т.А.; Matvienko, T. (Харків : Харківський національний університет імені В.Н. Каразіна, 2019)
У дисертаційному дослідженні комплексно проаналізовано політику Тимчасового уряду та Української Центральної Ради щодо земств, еволюцію ставлення останніх до суспільно-політичних процесів Української революції та національного державотворення. Досліджено особливості демократизації земств на весні 1917 року та під час виборів до волосних, повітових і губернських органів самоврядування сільського населення влітку ‒ восени 1917 року. Визначено вплив більшовицького Жовтневого перевороту 1917 року в Петрограді на земства України, наслідки агресії більшовицької Росії в Україну для земських органів Української Народної Республіки. З’ясовано особливості функціонування органів земського самоврядування УНР за присутності на її території австронімецьких військ. В диссертационном исследовании комплексно анализируется политика Временного правительства и Украинской Центральной Рады относительно земств, эволюция отношения последних к общественно-политическим процессам Украинской революции и национального строительства государства. Исследованы особенности демократизации земств весной 1917 года и вовремя выборов в волостные, уездные и губернские органы самоуправления сельского населения летом ‒ осенью 1917 года. Определено влияние большевистского Октябрьского переворота 1917 года в Петрограде на земства Украины, последствия агрессии большевистской России в Украину для земских органов Украинской Народной Республики. Выяснены особенности функционирования органов земского самоуправления УНР в присутствии на ее территории австрогерманских войск.
Zemstvos of Ukraineon the Background of Social and Political Processes in Ukraine of the Central Council Period (March 1917 - April 1918)
Matvienko T. Zemstvos of Ukraineon the Background of Social and Political Processes in Ukraine of the Central Council Period (March 1917 - April 1918) – Qualification research work on the rights of a manuscript. The thesis for the degree of Candidate of Historical Sciences specialty 07.00.01 "HistoryofUkraine",V.N. Karazin Kharkiv National University, Kharkiv, 2019. The influence of socio-political processes in Ukraine of the Central Council period (March 1917 ‒ April 1918) on zemstvos and their reverse impact on social and political transformations and Ukrainian statemaking process of that time are comprehensively analysed in this research work. The Interim Government and the Ukrainian Central Council zemstvo policy, the attitude evolution of the latter state body towards social and political processes of the Ukrainian revolution are analysed. The reasons of support for the Interim Government, created after the Russian autocracy overthrow, by the most part of Ukrainian zemstvos are substantiated. Its attempts to base on district and provincial zemstvos in developing local administrative authorities are analysed. Based on the analysis of social and political attitudes of the democratic population circles, the falsity of the Interim Government appropriate expectations are proved.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects; Ukrainian Central Council; the Interim Government; zemstvo; selfregulation; public committees; election; zemstvo assembly; zemstvo councils; power; the Bolsheviks; Українська Центральна Рада; Тимчасовий уряд; земство; самоврядування; громадські комітети; вибори; земське зібрання; земські управи; влада; більшовики